Upaya Meningkatkan Keterampilan Membaca Dengan Menggunakan Metode Reading Aloud Di Kelas III SDN Karangjengkol 01 - Mahdalena; Aris Naeni Dwiyanti; Inayatul Lathifah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Reading skills are one of the fundamental language competencies that elementary school students must master because they support learning across various subjects. However, the reading skills of third-grade students at SDN Karangjengkol 01 were still relatively low, as reflected in students' difficulties with reading fluency, pronunciation, intonation, and confidence when reading aloud. This study aimed to improve students' reading skills through the implementation of the Reading Aloud method. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consisted of planning, action, observation, and reflection conducted in two cycles. The participants were 20 third-grade students of SDN Karangjengkol 01. Data were collected through observation, reading performance assessments, documentation, and field notes, and were analyzed using descriptive qualitative and quantitative techniques. The findings revealed that the implementation of the Reading Aloud method successfully improved students' reading skills. Students demonstrated better reading fluency, more accurate pronunciation, appropriate intonation, and greater confidence in reading aloud. In addition, student participation during the learning process increased significantly. Therefore, the Reading Aloud method can be considered an effective instructional strategy for improving reading skills in elementary school students.